Multiprofessional approaches in the treatment for multiple sclerosis: a literature review - Barros Santos, Nágila; Santana Santos, Milena; Figueredo Sodré, Duanne; Andrade Pinheiro, Paloma (Seven Editora, 2023)
According to epidemiological data, more than 2.5 million people worldwide have Multiple Sclerosis (MS), which is known as a demyelinating disease that occurs in the Central Nervous System (CNS), being considered a progressive autoimmune disease, and may affect mostly women aged between 20 and 55 years, with no scientific evidence of prevention or cure until then. DOI: https://doi.org/10.56238/tfisdwv1-134